Hambatan-Hambatan Mahasiswa Program Studi Pendidikan Bahasa Inggris dalam Kemampuan Berbicara Khususnya Pada Mata Kuliah Speaking - Sariwati Muhamad; Hariyanti Djafar (Peneliti.net, 2020)
This study aims to identify what obstacles are encountered by students in speaking, especially in speaking subjects. The type of this research is qualitative research. The subject of this research is students in semester 3 (three) of English Education Study Program, Bumi Hijrah University, Maluku Uatara. This type of research is qualitative research. Where data is obtained through observation and interviews. The results of this study indicate that students of the English language education study program have obstacles in learning. These obstacles are in the form of 1. internal barriers which include: linguistic components (mental / fear, sentence composition, description / pronunciation and intonation, word selection, vocabulary / vocabulary). Content component (content relationship with topic). 2. External Barriers which include: Room conditions and knowledge of listeners. 3. Learning which includes: Learning methods and motivation.